Comparative Analysis of Natural Fibre Reinforced Composite Material Using ANSYS - K. G. Saravanan; R. Prabu; A. Sivapragasam; Nahom Daniel (Advances in Materials Science and Engineering)
The regulations of legislative bodies regarding the recycling and reusage of automotive materials has caused a great deal of obligation among automotive manufacturers to use natural fibres or green composites. Green composites or more commonly known as bio-composites are made up of natural fibres. Natural fibres are used by humankind since prehistoric times. The natural fibre is obtained from plants as well as animals. Since the natural fibre is obtained from natural as well as biological resources, it is biodegradable and recyclable. This paper presents the study and analysis conducted to address the suitability of natural fibre in the automotive industry. This paper discusses the finite element analysis of four different natural fibre composites used for making car door panel, i.e., flax, jute, sisal, and leather are taken for the material study. This paper helps to find the effectiveness of each of the four natural fibre composites that have already been used in the automotive sector. This paper includes the analysis of four different natural fibres with and without the addition of the aluminium as the reinforcement material. This project revolves around the design of the composite fibre sheet and analysis of the mechanical parameters such as equivalent stress, shear stress, strain, deformation, and so on. The studies and observations of the analysis showed that the natural fibre with the aluminium reinforcement proved to be much stronger than that without the reinforcement. The results of finite element analysis showcased lowest total deformation and equivalent strain in the flax as 1.026 m and 0.017 mm/mm, respectively. However, sisal showed the lowest equivalent stress and shear stress which were 68.09 and 38.178 MPa, respectively. Additionally, leather showed the highest amount of stress, strain, and deformation, and hence leather was deemed to have undesirable properties regarding the usage in car door panels. All the materials except leather were found to be safe under the loading conditions. Hence, the flax fibre is recommended by the project to have superior properties compared to the other materials.